Intelligent control of battery energy storage for microgrid energy management using ANN - Younes Boujoudar; Mohamed Azeroual; Hassan Elmoussaoui; Tijani Lamhamdi (International Journal of Electrical and Computer Engineering (IJECE), 2021)
In this paper, an intelligent control strategy for a microgrid system consisting of Photovoltaic panels, grid-connected, and li-ion battery energy storage systems proposed. The energy management based on the managing of battery charging and discharging by integration of a smart controller for DC/DC bidirectional converter. The main novelty of this solution are the integration of artificial neural network (ANN) for the estimation of the battery state of charge (SOC) and for the control of bidirectional converter. The simulation results obtained in the MATLAB/Simulink environment explain the performance and the robust of the proposed control technique.